Fast watermarking scheme for real-time spatial scalable video coding - Buhari, A.; Ling, Huo Chong; Baskaran, V.; Wong, K. (2016)
Recent advancements in high resolution scalable video coding have significantly increased the computational complexities of watermarking solutions for real-time video encoding systems. This paper proposes a human visual system based watermarking algorithm for spatial scalable coding based on the H.264/SVC standard. The proposed algorithm extracts textural feature from a set of 7 high energy quantized coefficients in 4×4 luma INTRA-predicted blocks of all slices and embeds watermark into the highly textured block which has at least one non-zero coefficient in 6 selected locations. The same embedding process is performed for all layers of the video to improve robustness against common video processing attacks. Experiments were conducted by embedding up to 8192 watermark bits into a four-layer spatial scalable coded video. Results suggest that the proposed scheme produces watermarked video with an average visual quality degradation of ~0.36 dB at the expense of 2.18% bitrate overhead. In addition, the proposed watermarking scheme achieves an average detection rate of 0.98, 0.97 and 0.71 against re-encoding, recompression and Gaussian filtering attacks, respectively, using the base layer, and above 0.97, 0.94 and 0.66, respectively when using any of the enhancement layer.